Estimation of Bundle Sheath Cell Conductance in C4 Species and O2 Insensitivity of Photosynthesis. - Brown, R. H. (1993)
Low conductance to CO2 of bundle sheath cells is required in C4 photosynthesis to maintain high [CO2] at the site of ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco). Elevated [CO2] allows high CO2 assimilation rates by this enzyme and prevents Rubisco oxygenase activity and O2 inhibition of carboxylation. Bundle sheath conductance to CO2 was estimated by chemically inhibiting phosphoenolpyruvate carboxylase and calculating the slope of the linear response of leaf CO2 uptake to [CO2]. The inhibitor 3,3-dichloro-2-dihydroxyphosphinoylmethyl-2-propenoate was supplied to detached leaves of Panicum maximum, Panicum miliaceum, and Sorghum bicolor at 4 mM. Uptake of CO2 was measured at 210 mL L-1 O2 over the CO2 concentration range of 0.34 to 28 mL L-1. Without the inhibitor, CO2 uptake increased steeply at low [CO2] and saturated at about 1 mL L-1. After inhibition, CO2 uptake was a linear function of [CO2] over much of the range tested. The slope of this CO2 response, taken as bundle sheath conductance, was 2.35, 1.96, and 1.13 mmol m-2 s-1 for P. maximum, P. miliaceum, and S. bicolor, respectively, on a leaf area basis. Conductance based on bundle sheath area was 0.76, 0.93, and 0.54 mmol m-2 s-1, respectively. Uptake of CO2 by leaves of P. maximum supplied with the inhibitor was not affected by reduction of [O2] from 210 to 20 mL L-1 over the range of [CO2] used. Because [CO2] in bundle sheath cells of inhibited leaves is likely to be much lower than ambient, the lack of O2 sensitivity of CO2 uptake cannot be ascribed to lack of O2 reaction with ribulose bisphosphate and is probably due to the low conductance of bundle sheath cells, especially at low ambient [CO2]. The likely result of reducing [O2] from 210 to 20 mL L-1 is to stimulate carboxylation of ribulose bisphosphate, thus further reducing [CO2] in bundle sheath cells and increasing CO2 diffusion to these cells from the mesophyll. However, the increase in diffusion is greatly limited by low conductance of the bundle sheath cell walls. Calculations based on estimated bundle sheath conductance show that changes in bundle sheath [CO2] of 0.085 to 0.5 mL L-1, which might be associated with reduced [O2], would have a negligible effect on CO2 uptake.